NETRALITAS APARATUR SIPIL NEGARA DALAM PEMILU SERENTAK TAHUN 2024 - amir; Hertanto (Halu Oleo University, 2023)
To increase neutrality, the government has made various arrangements to limit the relationship between Civil Servants (PNS) and practical political activities. Still, every General Election activity is always coloured by widespread reporting about neutrality violations by unscrupulous Civil Servants. This research aims to determine the Neutrality of The State Civil Apparatus In The Convenient Elections In 2024. This research method uses descriptive qualitative data from reviewing documents, observations, and interviews with Bawaslu of Central Lampung Regency. As a result, the neutrality of ASN is heavily influenced by the wishes of legislators. Public officials, whether from politics or independence, should not place ASN as a tool to maintain their power. Furthermore, regulations are needed in the context of tightening access for public officials to abuse authority, as well as providing access to strict supervision from parties, including internal ASN, to be able to report all forms of intervention. ASN should have a neutral nature in politics to protect society. ASN must also be free from the influence and intervention of all groups from political parties; this must be strictly prevented because it can lead to self-interest in practical politics